Pre-Study: Innovation in Chemistry Learning Base Interactive Virtual Lab - Elvi raziana (Proceeding of the International Conference on Mathematical Sciences, Natural Sciences, and Computing, 2024)
This study aims to identify the problems faced by students in implementing learning. This study used a quantitative approach with a survey method, involving 30 students from two high schools in Yogyakarta. Data were collected through questionnaires about students' learning difficulties, interests, and needs for learning media. The results showed that 96% of the students considered chemistry as a difficult subject to understand because of the abstract nature of the material. As many as 64% of the students felt bored due to the uninteresting presentation of the material, while 72% of the students indicated the need for varied learning methods and interactive learning media to facilitate understanding. The results of the study showed that an innovation was needed to support chemistry learning activities to make learning more active and enjoyable so that it does not lead to student boredom. The developed virtual laboratory media provides flexible, safe and economical simulation of chemical experiments. This application is designed to be accessible without an internet connection using an Android device, allowing students to learn anytime and anywhere. The use of this virtual lab is expected to increase students' motivation, understanding of concepts, and learning experience.